Metabolomics profiling and biological properties of root extracts from two Asphodelus species: A. albus and A. aestivus. (August 2020) - Lazarova, Irina; Zengin, Gokhan; Sinan, Kouadio Ibrahime; Aneva, Ina; Uysal, Sengul; Picot-Allain, Marie Carene Nancy; Aktumsek, Abdurrahman; Bouyahya, Abdelhakim; Mahomoodally, Mohamad Fawzi
Graphical abstract: Highlights: Different solvent extracts for two Asphodelus species were investigated. Enzyme inhibition and antioxidant capacity tested. Chemical profiles were detected by UHPLC/Orbitrap MS analysis. Flavonoids, anthraquinones, and phenolic acids were found. Aloin A & B and aloesin were identified from the methanol extract. Abstract: The pharmacological properties of Asphodelus species have been advocated previously. In this respect, the present study attempts to unravel the antioxidant and enzyme inhibitory activity of root extracts of two Asphodelus species, namely, A. albus and A. aestivus . Data gathered demonstrated that the dichloromethane (25.49, 51.30, 104.31, and 81.58 mg Trolox equivalents [TEs]/g, for 2, 2-diphenyl-1-picrylhydrazyl [DPPH], 2, 2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) [ABTS], cupric ion reducing antioxidant capacity [CUPRAC], and ferric reducing antioxidant power [FRAP] assays respectively) and ethyl acetate (20.60, 41.86, 89.07, and 57.85 mg TEs/g, for DPPH, ABTS, CUPRAC, and FRAP assays respectively) extracts of A. albus roots showed highest radical scavenging and reducing potential. These findings were in accordance with total phenolic content observed which showed the highest phenolic content of A. albus dichloromethane (30.74 mg gallic acid equivalents [GAEs]/g) and ethyl acetate (23.41 mg GAEs/g) extracts. Interestingly, A. albus and A. aestivus root extracts were active inhibitors of tyrosinase and lipase, with values varying from 56.52 to 71.49 mg kojic acid equivalent/g and 34.88 to 86.32 mg orlistat equivalent/g, respectively. Flavonoids, anthraquinones, and phenolic acids were identified as main individual compounds in chemical profile analysis. This is the first report of the presence of aloin A, aloin B, and aloesin in species other than in Aloe . Scientific evidences gathered from this study claimed the biological activity of the studied Asphodelus species and provided rationale for further investigations which might lead to the development of novel pharmacophores to alleviate oxidative stress related complications, obesity, as well as, skin hyperpigmentation complications.